The clinical picture of early-stage Parkinson’s disease. errors in the diagnosis of different forms - E N Gubanova; Natalia Vladimirovna Fedorova (Неврология, нейропсихиатрия, психосоматика)
The paper describes the clinical picture of Parkinson’s disease (PD), by indicating its stages in accordance with the classifications by different authors. It gives clinical diagnostic criteria for PD and indicates difficulties in making its correct diagnosis. Clinical examples were used to demonstrate misdiagnosed cases confirming a variety of the clinical symptoms at PD onset, which suggest that there is the need for a thorough patient examination and history data collection.